‘Lockdown Work’ - Bianca Tame; Zukiswa Zanazo (The Thinker)
This article explores domestic workers’ experiences of ‘lockdown work’, which refers to working conditions during the level 5 to level 3 lockdown period in South Africa during the Covid-19 pandemic. Drawing on in-depth interviews with female black African South African and African migrant domestic workers from Zimbabwe and Malawi, the article provides crucial insights into how the pandemic altered existing working conditions and employment relationships. We use the sociological concept ‘boundary work’ to illustrate the relational dynamic and consequence of social and physical distancing during the pandemic. We argue that social and physical distancing deepened the public-private divide in employers’ private households and domestic workers’ intimate workplaces. The findings show that domestic workers experienced limited or no control over decisions regarding Covid-19-related protocols in their workplace, intensified workloads without additional remuneration, and felt voiceless regarding working conditions because they feared losing their jobs. The experience of lockdown work highlighted domestic workers’ vulnerability because of the asymmetrical and intimate nature of domestic work under new management imperatives that positioned most domestic workers as a high-risk group or perceived carriers of Covid-19. We conclude that the experience of personalism/maternalism and distant hierarchy as forms of boundary work undermined domestic workers’ sense of dignity and employment rights.